If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(3x-6)=6(4x=8)
We move all terms to the left:
8(3x-6)-(6(4x)=0
We multiply parentheses
24x-(64x-48=0
| (8y/3)-(2y/4)=-13 | | 7k=-2+8k | | 6p-2=4p | | 8w-10=9w | | 2q=-3q+10 | | -4b=-9-5b | | x/11=8/7 | | 9x+36=–9 | | 12=-8(2x-1)+20 | | 4y+7+6y=33 | | 63=1x | | -6+x/13=-4 | | 5x-4x-5=0 | | 2^2x-16·2x+64=0 | | 6x-8-5x+6=8x-9 | | 19x-7=17x+1 | | 5(y+15)=90 | | 3y+1.3=4.7 | | x2+6x–59=0 | | 3k-2=-2(k+2 | | -5y+8=(-7 | | v+12/9=3 | | 19x+5+100=180 | | 69+w+2w=180 | | y-13=-10 | | 91=4u+11 | | 11a=−16 | | 2x+120+60=180 | | 0=b+19 | | 2x+21=12-69 | | m+68/8=3 | | 0=2x^2+x+2 |